PENGARUH KETERANGAN SAKSI MAHKOTA TERHADAP PUTUSAN HAKIM DALAM MENJATUHKAN SANKSI DIPERSIDANGAN - Farzah, Asha; Deliana, Evi; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The use of crown witnesses as evidence in criminal cases is permissible because it is based on reasons of concern about the lack of evidence presented, especially with regard to criminal cases in the form of inclusion and also reasons to fulfill a sense of public justice. The normative use of crown witnesses in the process of examining criminal cases does not clearly stipulate, but their use is recognized. The background presented by the witnesses of the crown is caused by the testimony of the witnesses of the crown is something that he saw himself and he did himself with his colleagues. Although his testimony feels burdensome to the other suspects even himself.The type of research is normative research by research into legal principles. This study uses a secondary data source consisting of primary legal materials, secondary legal materials, and tertiary legal materials, data collection techniques in this study with literature studies.From the results of the research problem there are two main things that can be concluded. First, the influence of the crown witness's statement on the judge's decision in imposing sanctions at the trial can be said to assist the judge in deciding the verdict on a case in which there is a lack of valid and sufficient evidence. Second, the judge's consideration of sanctioning the crown witness in the judge's decision is to accept formal facts with valid evidence and determine them based on the judge's conviction so that the judge's decision on a case can determine the fate of the defendant / kroon geituge.Keywords: Kroon getuige- Judge's decision- Sanctions